Improving Education Quality and Teacher Performance Through Benchmarking Implementation - Rosmayanti, Ervi; Prajanti, Sucihatiningsih Dian Wisika; Wasino, Wasino; Mahmud, Amir (Proceedings of International Conference on Science, Education, and Technology, 2024)
Quality education is essential in developing the potential of future generations. To achieve high quality education, the role of teachers as the spearhead in the learning process. One strategy that can be implemented to improve the quality of education and teacher performance is the implementation of benchmarking. This research aims to determine the importance of benchmarking in improving the quality of education and teacher performance. By comparing best practices and existing standards, benchmarking allows educational institutions to identify their strengths and weaknesses and adopt effective strategies for continuous improvement. This research also explores the various benchmarking methods that can be applied in the context of ranging from internal comparisons between units in a school to external comparisons with other educational institutions that have been successful in achieving similar goals. Results from implementation of benchmarking in education show that benchmarking can improve the quality of learning, curriculum development, as well as the improved teacher performance and motivation. However, the challenges of adapting best practices from other institutions as well as implementing changes in a dynamic educational environment are also focused on in this study. In conclusion, the implementation of benchmarking has great potential to improve education quality and teacher performance. In this context, collaboration, customization and a commitment to continuous improvement are key in optimizing the benefits of the benchmarking process to achieve education quality.